Possibility of COVID-19 Reinfection with Clinical Manifestation of Stroke: A Case Report - Aulia, Septy; Arisetijono, Eko; Yueniwati, Yuyun (Journal Of Cardiovascular, Neurovascular & Stroke, 2021)
Background: A new strain of RNA human coronavirus named SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) was first detected in December 2019 and became pandemic, infected millions of people worldwide, and responsible for a large number of deaths.1 Globally, as of 30th August 2020, there have been 24.822.800 confirmed cases of COVID-19, including 838.360 deaths, reported to WHO.2 SARS-CoV-2 virus can spread from the respiratory to the central nervous system because it has neuroinvasive abilities. Some patients with COVID-19 reported have neurological symptoms, such as anosmia, headache, dizziness, dysgeusia, and impaired consciousness. The information on SARS-CoV-2 recurrence or reinfection is still limited. We report a case of COVID-19 with stroke manifestation and a history of positive COVID-19 before and possibility reinfection of the disease. Case presentation: A man, 55-years old, came to the emergency department with a medical history of diabetes mellitus on insulin, hypertension, and a history of the acute coronary syndrome. He was first diagnosed with COVID-19 based on his nasopharyngeal swab without any clinical manifestation, then isolated himself in his home. His second and third nasopharyngeal swabs then showed negative results, and he was declared cured of COVID-19 infection. After 13 days, he returned to the emergency department with acute onset left-sided hemiparesis, dysarthria, and left-sided facial drop. The patient denied fevers, cough, nor dyspnea symptoms. His laboratory studies were within normal limits, but his antibody. Anti-SARS-CoV-2 showed a reactive result, confirmed by his nasopharyngeal swab with a positive result, and then he was diagnosed with COVID-19. His chest radiography showed normal results, and his head CT scan showed ischemic in the right insular lobe and ischemic in the right parietal lobe with senile brain atrophy. He was hospitalized in the high care unit for COVID-19 patients on the same day. He received treatment for stroke and COVID-19 infection with supportive care. Five days since admission, the patient spontaneously became hypoxic and somnolence with oxygen saturation 60% at that time, and the patient finally died due to respiratory failure. Conclusion: We report the case possibility of COVID-19 reinfection with clinical manifestation acute onset left-sided hemiparesis, dysarthria, and left-sided facial drop, without any manifestation of COVID-19 like fever, cough, dyspnea nor sore throat, and we diagnosed as stroke attack. The patient showed reactive rapid antibody Anti-SARS-CoV-2 and nasopharyngeal swab with a positive COVID-19. The patient has been diagnosed with COVID-19 one month before admission, his second and third nasopharyngeal swabs then showed negative results, and he cured of COVID-19 infection after that. We hypothesize the manifestation of stroke as a neurological manifestation of COVID-19 without any respiratory manifestation before. Unfortunately, we did not perform specific antibody IgM/IgG testing to differentiate whether this is the disease's reinfection or recurrence.